Risk Factors and Potential Economic Losses Associated with Stunting in Toddlers in Ogan Komering Ilir Regency - Rahmiwati, Anita; Ahmad Rivai (Department of Nutrition, Faculty of Health Sciences, Universitas Brawijaya Malang, 2023)
Stunting, a chronic condition arising due to nutritional deficiencies during pre- and postpartum periods, is a significant public health issue in Indonesia, with a nationwide prevalence of approximately 29.6% and about 22.6% in Ogan Komering Ilir Regency. This research aimed to identify the risk factors associated with stunting in toddlers aged 12-35 months and calculate the economic losses incurred by this condition. To achieve this, a cross-sectional design was employed. The population in this study were toddlers aged 12-35 months in Pedamaran sub-district, Ogan Komering Ilir Regency. A sample of 77 toddlers were selected through simple random sampling. Data were collected using questionnaires, and calculations based on the Konig 1995 and Horton 1999 formulas were used to analyze the Gross Regional Domestic Product (GRDP) per capita. The research found a stunting prevalence rate of 51.9% in toddlers. Additionally, dietary diversity emerged as a significant factor related to stunting (p-value of 0.0001) and was identified as the most dominant factor. In contrast, economic status, toddler participation, and history of infectious diseases were not significantly related to stunting (p-value > α). The estimated potential economic losses incurred by stunting amounted to IDR 170 billion and IDR 765 billion, respectively, or 0.67%-3.03% of OKI’s GRDP, resulting from a 2% and 9% decrease in productivity. Hence, this research suggests that food consumption diversity is the most dominant factor significantly related to stunting in toddlers in Ogan Komering Ilir Regency.